Analysis of MSME's Financial and Business Improvement Model through Digital Economy Services and Fintech Strategy - Subkhan, Farid; Maarif, Mohammad Syamsul; Rochman, Nurul Taufiqu; Nugraha, Yudhistira (Jurnal Aplikasi Manajemen, 2024)
The development of digital technology contributes significant roles to businesses, including micro, small, and medium enterprises (MSMEs). It raises the digital economy and fintech services to the MSMEs market, such as peer-to-peer lending, digital payment, crowdfunding, digital assets, e-commerce, social commerce, etc. This research aims to analyze MSMEs financial and business improvement model by using MSME's digital economy products and fintech penetration strategy in Indonesia. This study employed a mixed research method by integrating the Delphi technique and the Analytical Hierarchy Process (AHP). The Delphi method was used to identify criteria or construct for the research framework, while AHP was used to evaluate and determine the score and priorities of the MSMEs financial performance criteria, business goals, digital economy's alternative products, and fintech penetration strategies. The Delphi method consists of round 1 - to explore the research framework, round 2 - to rank the research indicators, followed by AHP at round 3. The study involves 20 expert panels of MSMEs in greater Jakarta. This study found that the use of digital economy products - particularly fintech will enhance MSMEs' financial performance by increasing sales volume and business profits. It helps them achieving business goals by increasing their revenue and expanding their business. MSMEs need digital payment and mobile banking as vital fintech services. This study also provides strategic guidance to fintech players and government to effectively penetrate fintech products to MSMEs mainly through knowledge dissemination and digital knowledge improvement.